The law and ethics of restitution / Hanoch Dagan. - Dagan, Ḥanokh (Cambridge University Press, 2004)
Dagan's 2004 book provides a dynamic account of the American law of restitution. The book reviews the existing doctrine, using an ethical perspective to expose and examine critically the normative underpinnings of the core categories of restitution. Dagan also discusses some of the most controversial issues in the area, such as cohabitation, improper tax payments, and the role of constructive trusts as trumps in bankruptcy. He further tackles the recent restitution claims of slave laborers (or their descendants) against corporations that benefited from their enslavements, and of governmental bodies against injurious industries. Dagan argues that the concept of unjust enrichment is not an independent reason for restitution but, rather, serves as a loose framework. By integrating doctrinal and ethical analyses of restitution across the spectrum of restitution contexts, the author offers significant and provocative insights on existing law as well as possible reforms.